Suitability Of Groundwater for Irrigation in the southern part of Wadi Atlal in Sirte - Omran Ali hamed Amshaher; Hassin .A.Makhlof; Ammar Abd Alraheem Abdulhadi Zan (Journal of Pure & Applied Sciences, 2022)
The main objective of this study is to evaluate the groundwater in Katwara area located at Southern Atlal Valley for the agricultural purpose, where 10 samples wells were randomly distributed throughout the study area. The samples were collected and chemical analyzes of the samples were carried out, and the results were classified and evaluated based on the classification of the American Salinity Laboratory USSL 1954 and FAO 1985 classifications. The results showed that water classified according to (USSL), as wells 7, 8, 9 and 10 are located within the classification of C4-S1, while wells 3,4 and 6 are located within category C4-S2. Whereas, wells 5 and 2 are located under the category C4-S3 and C3-S1 respectively. FAO classification data declared that, all tested samples of PH are suitable for crops irrigation with no damage(6.5-8.4).The parameter of salinity indicated that samples fell within the class of (Few to moderate hazard) for wells 2 , 7 , 8 , 9 , 10 .While wells 1,3,4,5,6 fell within the class (increase in salinity hazard) . Data of (SAR) reported that wells (2,4,7,9,10) fall within the second classification which higher than 9 with the risk groups of slight-moderate damage for plants, while wells (1,3,5,6,8) fall within the second classification so the sodium problem will be severe. Classification of HCO 3 -2 declared that all values are ranged between (1.5-8.5 meq/L), so there is slight-moderate risk for irrigation use..As well, the results showed that the percentage of chloride exceeded the limit by 10 meq /L most of the wells, except sample No. 2, which falls in the second category, confined between 4-10 meq / l.